a)(x-2)²=x²
x²-2*2х+2²-x²=0
4-4х=0
-4х=-4
х=-4:(-4)
х=1
б)(3y+5)²=9y²
9y² +2*5*3у+5²-9y² =0
30у+25=0
30у=-25
у= -25:30
у= -25\30= - 5\6= - 0,8(3)= -0,83
в)(c-7)²=c²-7
c²-2*7с+ 49-c²+7=0
-14с+56=0
-14с= -56
с= -56: (-14)
с=4
г)(6-z)²=z²+36
36-2*6z+z²-z²-36=0
-12z=0
z= 0: (-12)
z=0
д)(2x-1)²+2=0
4x²-2*2х+1+2=0
4x²-4х+3=0
D=b²-4ac=(-4)²-4*4*3=16-48= -32<0 - нет корней
е)3(x-2)²=3
3(x²-2*2х+4)=3
x²-4х+4=3:3
x²-4х+4=1
x²-4х+4-1=0
x²-4х+3=0
D=b²-4ac=(-4)²-4*1*3= 16-12=4
х1= -b+√D\2а=(4+√4):2=(4+2):2=6:2=3
x2= -b-√D\2а= (4- √4):2= (4-2):2=2:2=1
Пошаговое объяснение:
х-4=2
х-4=-2
х=6
х=2;
2)|у+5|=3
у+5=3
у+5=-3
у=-2
у=-8;
3)|3+х|=1,5
3+х=1,5
3+х=-1,5
х=-1,5
х=-4,5
4)|7-у|=-2-выражение ложно;
5)|х+3|+4=9
|х+3|=9-4
|х+3|=5
х+3=5
х+3=-5
х=2
х=-8;
6)|у-2|+8=5
|у-2|=5-8
|у-2|=-3-выражение ложно.